Performance analysis of structured peer-to-peer overlays for mobile networks. Issue 5 (3rd September 2017) - Chowdhury, Farida; Furness, Jamie; Kolberg, Mario
Abstract: Distributed Hash Table (DHT) based Peer-to-Peer (P2P) overlays have been widely researched and deployed in many applications such as file sharing, IP telephony, content distribution and media streaming applications. However, their deployment has largely been restricted to fixed, wired networks. This is due to the fact that supporting P2P overlays on wireless networks such as the public mobile data network is more challenging due to constraints in terms of data transmissions on cellular networks, limited battery power of the handsets and increased levels of node churn. However, the proliferation of smartphones makes the use of P2P applications on mobile handsets very desirable. In this article, we have analysed and evaluated the performance and efficiency of five popular DHT based structured P2P overlays (Chord, Pastry, Kademlia, Broose and EpiChord) under conditions as commonly experienced in public mobile data networks. Our results show that the conditions in mobile networks, including a high churn rate and the relatively low bandwidth availability is best matched by Kademlia and EpiChord. These overlays exhibit a high lookup success ratio and low hop count while consuming a moderate amount of bandwidth. These characteristics make these two overlays suitable candidates for use in mobile networks. Graphical Abstract: